PERANAN SEKTOR AGROINDUSTRI TERHADAP PEREKONOMIAN KABUPATEN ROKAN HILIR: ANALISIS STRUKTUR INPUT-OUTPUT - Artika, Desy Tri; Bakce, Djaimi; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
In some countries, particularly developing countries, agroindustry is considered one of its driving force in the economy of the country. This research aims to analyze the role of agroindustry sector to the economy of lower Rokan through input-output structure of the review. The data used in this research in the form of input-output table on the basis of producer price in 2011 with 18 x 18 classification of sectors and sourced from Bappeda of Kabupaten Rokan Hilir. The research results showed: First, agroindustry have a high role to the economy of Kabupaten Rokan Hilir. The two sectors of the agro-industries which have a high contribution of the industrial sector is in a row of wood, sawn and processed, the industrial sector of food, beverages and tobacco. Second, from the output’s side, a component of the establishment of agro-industries sector output was more driven by investment, followed by exports and consumption. Third, from the input’s side, the sectors of agro-industries are more driven by the producer surplus, folowed by wage-salaries and intermediate input. Based on these result, in order to encourage economic growth in agro-industries then it needs to be an effort to increase investment either by government or businessmen through the accumulation of capital comes from the surplus business. One of attempts to increased the investment is accumulation of capital source from producer surplus. Keywords: the role of agroindustry sector, input-output table, producer surplus